On Initial Chebyshev Polynomial Coefficient Problem for Certain Subclass of Bi-Univalent Functions - Sakar, F. Müge; Doğan, Ertuğrul (Communications in Mathematics and Applications, 2020)
In this paper, we firstly, introduced the subclass \(R_Σ(τ ,α ,γ ;t)\) satisfying subordinate conditions. Subsequently, considering this defined subclass, initial coefficient estimations are established using by Chebyshev polynomials expansions, and Fekete-Szegö inequalities are also derived for functions belonging to the said subclass. Furthermore, Some relevant consequences of these results are also discussed.